2016
DOI: 10.1016/j.molcel.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Activation and Inhibition of the UCH37 Deubiquitylase

Abstract: In the original version of the above article, Table 2 reported that the UCH37(M148A/F149A)/RPN13 mutant complex has kinetic parameters indistinguishable from those of unbound UCH37. Further investigation of the UCH37 M148A/F149A construct revealed a gene duplication event that resulted in expression of a truncated protein product. Experiments repeated with the correct UCH37 M148A/F149A construct, in addition to a UCH37 M148D/F149D double mutant, reveal only a slight effect on the kinetic parameters. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…12). In support of our findings on BAP1/ASXL1/2, recent crystallography and molecular studies characterized the mechanism of activation of UCH37 by RPN13 (55,56). The most remarkable similarities with BAP1 are the conserved intramolecular interaction between the DEUBAD of RPN13 and the ULD of UCH37 and the stimulatory effect of RPN13 at the level of substrate binding.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…12). In support of our findings on BAP1/ASXL1/2, recent crystallography and molecular studies characterized the mechanism of activation of UCH37 by RPN13 (55,56). The most remarkable similarities with BAP1 are the conserved intramolecular interaction between the DEUBAD of RPN13 and the ULD of UCH37 and the stimulatory effect of RPN13 at the level of substrate binding.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, highly conserved amino acid residues in BAP1 and UCH37 are required for the interaction with the hydrophobic patch of ubiquitin. Finally, similar to ASXM, the DEUBAD of RPN13 also establishes a weak interaction with ubiquitin (55,56). Thus, BAP1 and UCH37 share a highly conserved mechanism of cofactor-mediated DUB activation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, UCH37 is also part of another complex, the chromatin-remodelling INO80 complex, in which its activity is inhibited (Yao et al, 2008). Elegant structural studies have revealed that equivalent DEUBiquitylase ADaptor (DEUBAD) domains present in both Rpn13 (also known as ADRM1 in mammals) and INO80G (also known as NFRKB) induce distinct structural rearrangements in UCH37 that result in its activation at the proteasome and inhibition at the INO80 complex, respectively (Sahtoe et al, 2015;VanderLinden et al, 2015).…”
Section: Interacting Partners Of Dubsmentioning
confidence: 99%
“…Apo UCH37 may exhibit some conformational flexibility, but binding of INO80G places the enzyme into an inactive state by both blocking the ubiquitin-binding site and disrupting alignment of the active site. By contrast, binding to RPN13 increases activity above that of unliganded UCH37 by constraining the enzyme's crossover loop and increasing affinity for ubiquitin (98,99).…”
Section: Deubiquitinases Are Surprisingly Flexible Scissorsmentioning
confidence: 99%